Poligami Dalam Konteks Perselingkuhan: Analisis Pasal 3 UU No.1 Tahun 1974 dan Maqashid Syariah - Solihat, Naysila Fitri; Arifin, Tajul (STIS DAFA MATARAM, 2025)
Polygamy remains a contested issue in Islamic family law, particularly when it intersects with infidelity. This study analyzes the regulation of polygamy under Article 3 of Law No. 1 of 1974 on Marriage through the lens of Maqashid Shariah, using a normative-empirical juridical approach. Primary legal sources include the Marriage Law, the Compilation of Islamic Law (KHI), Supreme Court Regulation No. 3 of 2019, and Maqashid Shariah principles. Secondary sources include reports from the Supreme Court (2023), LBH APIK (2022), and Komnas Perempuan (2021), alongside relevant academic literature. The findings reveal two central problems: first, legal loopholes in Articles 3–4 are systematically exploited to legitimize relationships originating from infidelity, particularly through the misuse of the